Evaluation of macular perfusion in patients with treatment-naive overt hypothyroidism using optical coherence tomography angiography - Mavi Yıldız, Ayşegül; Şahingöz Erdal, Gülçin; Tarakcioglu, Hatice; Yıldız, Ali Atakhan; Yılmaz, Sami (Journal of Surgery and Medicine, 2021)
Background/Aim: Thyroid hormones play an essential role in retinal development and physiological functions. Although the effects of hyperthyroidism on ocular circulation are well-defined, no studies report the effects of clinical hypothyroidism on retinal and choroidal circulation. We aimed to compare the macular vessel density and flow indexes of patients with treatment-naive hypothyroidism and healthy controls using optical coherence tomography angiography (OCTA). Methods: This case-control study included 104 eyes of 52 participants. Group 1 (n=24) consisted of patients with treatment-naive overt hypothyroidism, while Group 2 (n=28) consisted of age and sex-matched healthy controls. Images were obtained using AngioVue software 2.0 of the OCTA device in a 6 × 6 mm area centered on the macula. Foveal avascular zone (FAZ) area, macular retinal thickness, FAZ perimeter (PERIM), choroidal flow index (CF), outer retinal flow index (ORF) and macular vessel density (VD) in the superficial (SCP) and deep retinal capillary plexus (DCP) were recorded for all patients. Results: The whole [Group 1: 49.9 (7.0)%; Group 2: 54.6 (5.9)%], parafoveal [Group 1: 54.7 (4.8)%; Group 2: 58.6 (3.9)%] and perifoveal [Group 1: 51.5 (7.2)%; Group 2: 55.9 (6.8)% ] VD in DCP were significantly lower in Group 1 compared to Group 2 (P=0.012; P=0.002 and P=0.028 respectively). However, parafoveal VD in SCP was significantly higher in Group 1 [52.4 (2.26)] than in Group 2 [49.9 (6.87)] (P=0.032). The mean VD in DCP was significantly positively correlated with the choroidal (P=0.021) and outer retinal flow indexes (P=0.033). The mean foveal VD in DCP was significantly positively correlated with the mean foveal (P<0.001), parafoveal (P=0.001) and perifoveal retinal thicknesses (P<0.001). Conclusion: Our study has provided, for the first time, a quantitative assessment of macular perfusion in patients with overt hypothyroidism using OCTA. The reduction in VD in the DCP might be attributed to the lack of angiogenic effects of T4 or neural hypometabolism secondary to hypothyroidism.